2011
DOI: 10.1007/s10616-011-9372-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 4-thujanol on chromosome aberrations, sister chromatid exchanges and micronucleus in human peripheral blood lymphocytes

Abstract: 4-Thujanol, a bicyclic monoterpene alcohol, is present in the essential oils of many medicinal and aromatic plants. It is commonly used as a fragrance and flavouring ingredient in a lot of different products. The potential genotoxic effects of 4-thujanol on human peripheral blood lymphocytes (PBLs) were investigated in vitro by the chromosome aberrations (CAs), sister chromatid exchanges (SCEs), and micronucleus (MN) tests. The cells were treated with 13, 26 and 52 lg/mL 4-thujanol in the presence and absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In contrast, the unconscious use of the plants in medicine could cause toxic (Qu et al 1992;Chiang et al 1997), mutagenic or cancerogenic effects (Gurley et al 2010;Háznagy-Radnai et al 2008;Rencuzogullari et al 2009;Buyukleyla and Rencuzogullari 2009;Kayraldiz et al 2010;Kocaman et al 2011). Azirak and Rencuzogullari (2008) also reported that thymol and carvacrol induced chromosomal abnormalities in bone marrow cells of rats.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the unconscious use of the plants in medicine could cause toxic (Qu et al 1992;Chiang et al 1997), mutagenic or cancerogenic effects (Gurley et al 2010;Háznagy-Radnai et al 2008;Rencuzogullari et al 2009;Buyukleyla and Rencuzogullari 2009;Kayraldiz et al 2010;Kocaman et al 2011). Azirak and Rencuzogullari (2008) also reported that thymol and carvacrol induced chromosomal abnormalities in bone marrow cells of rats.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the high frequency of chromosome aberrations may have triggered mitotic selection and pressured cell proliferation (Madle et al 1993;Vock et al 1998;Galloway et al 1998;Hillard et al 1998;Armstrong et al 1992;Kirkland and Muller 2000;Kocaman et al 2014). The cell death might have arisen from the oxidative stress and the high genotoxic effects that caused to apoptosis and necrosis which is the main mechanism of the cytotoxicity (Bakkali et al 2008;Kocaman et al 2011). Copper (Cu) is essential for many biological systems as a cofactor of enzymes including cytochrome C oxidase, tyrosinase, dopamine-b-hydroxylase, superoxide dismutase (Suzuki et al 2002;El-Gendy et al 2009) and it has a very important role in hemoglobin synthesis involved in Fe metabolisms (WHO 1974).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the CA assay showed that NAAm induced the more structural CAs (especially chromatid breaks and acentric fragments) than the numerical CAs. Hence, it can be suggested that NAAm has a clastogenic effect and can lead to the formation of structural CA by breaking the phosphodiester backbone of DNA (Kocaman et al 2011). DNA damage may be result of direct impact of NAAm on DNA or its indirect effect, for example by production of free radicals.…”
Section: Discussionmentioning
confidence: 99%